Emergent structure in unstructured epidemic multicast - Carvalho, Nuno (2007)
In epidemic or gossip-based multicast protocols, each node simply relays each message to some random neighbors, such that all destinations receive it at least once with high proba- bility. In sharp contrast, structured multicast protocols explicitly build and use a spanning tree to take advantage of efficient paths, and aim at having each message received exactly once. Unfortunately, when failures occur, the tree must be rebuilt. Gossiping thus provides simplicity and resilience at the expense of performance and resource efficiency. In this paper we propose a novel technique that exploits knowledge about the environment to schedule payload transmission when gossiping. The resulting protocol retains the desirable qualities of gossip, but approximates the performance of structured multicast. In some sense, instead of imposing structure by construction, we let it emerge from the operation of the gossip protocol. Experimental evaluation shows that this approach is effective even when knowledge about the environment is only approximate.